The plague - Camus, Albert, 1913-1960. (New York : Vintage Books, 1991)
Chaos prevails when the bubonic plague strikes the Algerian coastal city of Oran. A haunting tale of human resilience in the face of unrelieved horror, Camus' novel about a bubonic plague ravaging the people of a North African coastal town is a classic of twentieth-century literature.
Translation of: La peste.
Keywords: Plague -- Fiction; Psychological fiction